2013
DOI: 10.3390/rs5126667
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Bayesian Data Analysis in Radiometric SAR System Calibration: A Case Study on Transponder Calibration with RADARSAT-2 Data

Abstract: A synthetic aperture radar (SAR) system requires external absolute calibration so that radiometric measurements can be exploited in numerous scientific and commercial applications. Besides estimating a calibration factor, metrological standards also demand the derivation of a respective calibration uncertainty. This uncertainty is currently not systematically determined. Here for the first time it is proposed to use hierarchical modeling and Bayesian statistics as a consistent method for handling and analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Different methods were analytically compared [8] and conducted in order to increase calibration confidence through cross-comparisons. Thus, a standard uncertainty of 0.2 dB has been achieved [9][10][11]. • DLR's remote controlled trihedral corner reflector is shown in Figure 2b.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods were analytically compared [8] and conducted in order to increase calibration confidence through cross-comparisons. Thus, a standard uncertainty of 0.2 dB has been achieved [9][10][11]. • DLR's remote controlled trihedral corner reflector is shown in Figure 2b.…”
Section: Introductionmentioning
confidence: 99%
“…Although this value does not exclusively explain the difference between the three-transponder method and NWA curves, the sign and the general trend is certainly correct. Despite the encouraging findings for this first demonstration campaign, the derived combined RCS standard uncertainty of 0.38 dB is rather large in comparison to other measurement methods (e.g., 0.2 dB for measurements with corner reflectors (main uncertainty contributors) exploiting satellite overpasses, see [5]). Yet there is no reason in ascribing the uncertainty to the three-transponder method itself.…”
Section: Discussion Of Measurement Resultsmentioning
confidence: 65%
“…During this time, the transponder gain varies slightly despite the thermal control. Previous repeated measurements have shown that the transponder gain is stable within a standard uncertainty of 0.02 dB during 1 h intervals [5].…”
Section: Gain Drift Errorsmentioning
confidence: 91%
See 1 more Smart Citation
“…In Döring et al [10], a new method is applied for the systematic derivation of calibration uncertainties of synthetic aperture radars. This is an important step toward traceable radiometric calibration of these systems.…”
mentioning
confidence: 99%